PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN COMMUNITY BASED TOURISM (STUDI KASUS DESA WISATA KETAPANRAME KABUPATEN MOJOKERTO JAWA TIMUR) - Tamianingsih Tamianingsih; Deby Febriyan Eprilianto (Universitas Negeri Surabaya, 2022)
National development is an agenda that must be carried out to the village realm to distribute welfare. The application of village development using the concept of a tourism village requires the participation of the community, whose development can be done with Community-Based Tourism (CBT). One of the villages that applies the CBT concept is Ketapanrame Village, located in Trawas District, Mojokerto Regency, East Java. Researchers used descriptive research methods with a qualitative approach and also case studies. This study aims to describe the role of community participants who are members of community-based tourism in the management of the Ketapanrame Tourism Village. This research focuses on two community groups: KUB Taman Ghanjaran, and Pokdarwis Rakasiwi. Data collection techniques were carried out by interview, observation, and documentation. The results of this study are based on participation indicators according to Theresia in Hajar (2018), which consist of: (1) participation in decision making, KUB Taman Ghanjaran has the authority to regulate management and operations independently, while Pokdarwis Rakasiwi is limited to operations only; (2) participation in implementing activities in which the local society contributes business capital in the form of shares, and the communities contribute their energy to managing human resources, tourist attractions, and media promotions; (3) participation in monitoring and evaluation of development, the two community groups regularly hold evaluation meetings and report income to shareholders; and (4) participation in the utilization of development results which the people involved feeling that they get to benefit from getting jobs and dividends. Although community groups actively participate, there are still criticisms regarding parking services at Sumber Gempong Rice Fields Tourism. Therefore, it is necessary to provide assistance and training on hospitality for Pokdarwis Rakasiwi so that community groups can provide the best service in serving visitors. Of the three sub-villages, only Ketapanrame and Sukorame are used as tourist attractions and have management community groups. It is necessary to involve the Slepi community group to avoid social jealousy between sub-villages managing the Ketapanrame Tourism Village. Keywords: Community Participation, Community Based Tourism, Ketapanrame Tourism Village